1998
DOI: 10.1063/1.120938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cross-type bias in a two-dimensional array of short Josephson junctions

Abstract: We investigate numerically the effect of cross-type bias on two-dimensional arrays of short Josephson junctions. We have demonstrated that, for the simplest circuit, this type of bias is able to phase lock the junctions yielding a substantial improvement over ordinary biasing schemes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Thus, a rather different approach, such as those described in Refs. [17][18][19][20][21] is called for.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a rather different approach, such as those described in Refs. [17][18][19][20][21] is called for.…”
Section: Discussionmentioning
confidence: 99%
“…1͒ and vertically, i.e., all junctions in the array must be made to enter the voltage state. 28 Similar thinking led Filatrella, Pedersen, and Wiesenfeld 14 to study a 2ϫ2 array with identical junctions using what they described as a cross-type biasing. In contrast to the current injection scheme of Fig.…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3][4][5][6][7][8] Theoretical studies have begun to determine under what conditions and for what ranges of circuit parameters coherent emission should be possible from such arrays. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] These arrays are also of interest as paradigms of nonlinear dynamical systems with many degrees of freedom. [24][25][26][27] Of particular interest have been the so-called phaselocked states of such arrays.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] As test beds for both theoretical and experimental studies of synchronization of disordered oscillator systems, JJ arrays serve an important purpose, but in addition there has been interest for some time in arrays as sources of coherent microwave radiation. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] The experiments by Barbara and co-workers 31 demonstrated that two-dimensional, underdamped arrays in a high-Q resonance cavity formed by the array itself and a ground plane could emit coherent mm-wavelength radiation at power levels much higher than seen before. The main criteria for the high detected ac power output was a sharp resonance of the cavity and a coupling mechanism between the cavity and the individual JJs.…”
mentioning
confidence: 99%